Competitive risk analysis of the therapeutic value of liver transplantation for liver cancer in children: A population-based study - Xing, Huiwu; Yang, Chenyu; Tan, Bingqian; Zhang, Mingman (Frontiers in Surgery, 2022)
Background: Liver transplantation (LT) is one of the most important treatments for children with liver cancer (CLCa), and has been increasingly used. However, there is a lack of large-scale and multicenter studies on the trend in the application and value of LT for the treatment of CLCa. Methods: We analyzed the clinicopathological data of CLCa from 2000 to 2018 from the Surveillance, Epidemiology, and End Results (SEER) database. We explored the trend in the application of LT for the treatment of CLCa. LASSO Cox regression and the Log-Rank test were used to explore prognostic factors, and we built a nomogram using the screened factors. Propensity score matching (PSM) was used to balance the baseline data of patients undergoing LT and other surgeries, and then the Log-Rank test was used to evaluate the therapeutic value of LT for CLCa. Results: The 1 -, 3-, 5- and 10-year OS rates of CLCa were 88.7%, 80.6%, 76.8% and 73.0%, respectively. Then, we established a nomogram using many variables including age of diagnosis, regional lymph node metastasis, summary stage and therapy. Internally validated and externally verified, our nomogram had good predictive power and clinical applicability. LT was increasingly being used to treat CLCa. There was no statistically significant difference in the OS of CLCa between the LT and other surgeries groups. After LT, the HB group had a better prognosis than the HCC group. Conclusion: We built a well-performing nomogram to predict the OS of CLCa. LT could improve the prognosis of CLCa as other surgeries and could be considered an effective treatment choice for CLCa.